Pengaruh Penggunaan Media Scrapbook terhadap Hasil Belajar pada Pembelajaran Tematik Siswa Kelas IV SD Gugus X Kota Bengkulu - Indah Puspita Sari; Nani Yuliantini; Pebrian Tarmizi (Universitas Bengkulu, 2020)
The purpose of this study was to determine of effect of using scrapbook media on learning result in thematic learning. The type of research is quantitative. The research method is quasi experimental with the type of research design is nonequivalent pretest-posttest control group design. The population is class IV SDN group X Kota Bengkulu. The sample in this study were fourth grade students of SDN 04 and SDN 11 Kota Bengkulu. The technique used stratified random sampling. The instrument used was a multiple choice test. The test is taken before and after learning takes place in the control class and the experimental class. From the results of research and discussion, t-test results are known with a t-value of 4.51 and a table value of 2.02. So with tcount (4.51)> ttable (2.02) at a significant level of 5%, it can be concluded that there is an influence of the use of scrapbook media on thematic learning towards the learning outcomes of Indonesian students in class IV SD X in Bengkulu City.Keywords: Thematic Learning, Scrapbook Media, Learning result